Prevalence of Cervical Artery Abnormalities on CTA in Patients with Spontaneous Coronary Artery Dissection: Fibromuscular Dysplasia, Dissection, Aneurysm, and Tortuosity - Benson, J.C.; Lehman, V.T.; Verdoorn, J.T.; Shlapak, D.P.; Hayes, S.N.; Tweet, M.S. (American Journal of Neuroradiology, 2021)
BACKGROUND AND PURPOSE: Little is known about associations between spontaneous coronary artery dissection and cervical artery abnormalities. This study sought to assess the prevalence of cervical artery abnormalities among patients with spontaneous coronary artery dissection.MATERIALS AND METHODS: A retrospective analysis was completed of patients who underwent CTA neck imaging as part of arterial assessment following the diagnosis of spontaneous coronary artery dissection. The internal carotid and vertebral arteries were evaluated for the presence of fibromuscular dysplasia, dissection and/or pseudoaneurysm, ectasia and/or aneurysmal dilation, atherosclerosis, and webs. Carotid tortuosity was categorized into kinks, loops, coils, and retrojugular and/or retropharyngeal carotid courses; vertebral tortuosity was classified by subjective analysis of severity.RESULTS: Two hundred fourteen patients were included in the final cohort, of whom 205 (95.8%) were women; the average age was 54.4 years. Fibromuscular dysplasia was the most frequently observed abnormality (83 patients; 38.8%), followed by dissections and/or pseudoaneurysms (n = 28; 13.1%), ectasia and/or aneurysmal dilation (n = 22; 10.3%), and carotid webs (n = 10; 4.7%). At least 1 type of carotid tortuosity was present in 99 patients (46.3%). The majority (n = 185; 86.4%) of patients had no carotid atherosclerosis; and 26 (12.2%) had mild; 3 (1.4%), moderate; and 0, severe carotid atherosclerosis.CONCLUSIONS: The most common abnormality in the cervical artery vasculature of patients with spontaneous coronary artery dissection is fibromuscular dysplasia. Cervical dissections were higher than previously reported but were not observed in most patients.ACSacute coronary syndromeCTDconnective tissue disorderFMDfibromuscular dysplasiaSCADspontaneous coronary artery dissection